Athenry Castle, east interior wall of hall, window, hood - O'Donovan, Danielle (My University, 2008)
Hood of east window. Moulding comprises angle keel flanked by quarter hollows.
East window
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Medieval; keel moldings; moldings, hollow